Dinâmica populacional do caranguejo-uçá, Ucides cordatus (Linnaeus, 1763) (CRUSTACEA, BRACHYURA, UCIDIDAE) no município de Porto do Mangue, litoral norte do estado do Rio Grande do Norte - Alencar, Carlos Eduardo Rocha Duarte (2010)
Decapod crustaceans are one of the most important portions of megafaunal of coastal waters, playing a role as modifier of the environment and controlling populations of other organisms. Among the Decapoda, crab (brachyuran) constitutes the dominant macrofauna of mangroves. Among brachyuran is the mangrove crab (Ucides cordatus, Linnaeus, 1763), which represents the main component of the macrofauna of mangroves, particularly in Northern and Northeastern Brazil. In Brazil, its distribution is known from the state of Amapá to the north of Santa Catarina. This species is distinguished by its economic importance, being one of the main fishing resources in Brazil, generating a significant impact on their natural populations. This reduction would result in loss of value to the product, preventing its commercialization. Although it´s great ecological and economic importance, there are few articles about the biological aspects of U. cordatus, mainly in the state of Rio Grande do Norte. This work aimed to study the population dynamics of the mangrove crab, Ucides cordatus (Linnaeus, 1763), in Conchas estuary, Porto do Mangue, northern coast of Rio Grande do Norte. During the period November 2009 to October 2010 the crabs were collected monthly, obeying predetermined lunar periods (new moon or full moon) in a mangrove area in Porto do Mangue - RN. With the aid of a steel caliper (0.01 mm) and a precision balance (0.01 g) were measured biometric variables related to the animal's carapace, major propodus chela, width of abdomen (female), length of gonopodium ( males) and total weight. In addition, it was recorded, the gonads and molt stages, for males and females. In total, 476 crabs were collected, with 338 males and 138 females. Males were larger, heavier and in greater proportion than females. The reproductive period for the species in this location was limited during the months November to May, suggesting a change in current environmental legislation for the closure period. Synchrony was observed between the morphological and physiological maturity with females maturing earlier, possibly, a reproductive strategy adopted, compared to the low fishing pressure in the area. The molting period occurred in the dry season peaking in October. The analysis of growth, based on the parameters of von Bertalanffy was calculated using the nonlinear fit using modes (AJMOD). High growth rates for both males (L = 7.54 cm, k = 0.95, t0 =- 00:08; tmax = 4.84) and females (L = 6.50, k = 1 , 2, t0 =- 0008; tmax = 3.28) were found, contrasting with data from the literature, using other techniques. Males had higher asymptotic width size and longevity, but a lower growth constant when compared with females. The estimated age, for males and females, reaching the minimum capture size was 1.82 years and 1.63 years respectively. The size of physiological maturity, when individuals are able to reproduce, was estimated at 1.4 years and 1.05 years, for males and females, respectively. The recruitment period for this species is seasonal, with two peaks of occurrence, one in the rainy season and one in the dry season. This work represented the first effort on understanding the ecology of the mangrove crab, to the northern coast of Rio Grande do Norte. However, further studies on its biology should be undertaken, especially those related to growth, and recruitment, where observed that literature is more scarce